1975
DOI: 10.1007/bf00583833
|View full text |Cite
|
Sign up to set email alerts
|

Lactic acid permeation rate in working gastrocnemii of dogs during metabolic alkalosis and acidosis

Abstract: In isolated, blood perfused, supramaximally stimulated, isotonically working gastrocnemii of dogs lactic acid (LA) output and O2-consumption (V O2) were measured according to the Fick principle. Simultaneously concentration of muscle tissue was determined at rest and at different times during exercise. In one series of experiments metabolic alkalosis was induced by infusions of THAM of Na bicarbonate. As a result arterial pH increased to about 7.5 and standard [HCO3-1] to 31-35 mmol per 1. In another group of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
41
0
2

Year Published

1979
1979
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 118 publications
(45 citation statements)
references
References 20 publications
2
41
0
2
Order By: Relevance
“…Several researchers have shown enhanced membrane permeability to lactate as a result of extracellular alkalosis (18,40,41,63), but it is difficult to determine which factors cause this effect. Direct relations between lactate efflux and extracellular HCO3-concentrations have been shown (18,40,41,60), but these relations are clouded by the fact that extracellular Ht and HC03-concentrations are determined largely by strong ion concentrations (16). Thus these ionic concentrations and translocations may actually be the basis for the ergogenic effect.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several researchers have shown enhanced membrane permeability to lactate as a result of extracellular alkalosis (18,40,41,63), but it is difficult to determine which factors cause this effect. Direct relations between lactate efflux and extracellular HCO3-concentrations have been shown (18,40,41,60), but these relations are clouded by the fact that extracellular Ht and HC03-concentrations are determined largely by strong ion concentrations (16). Thus these ionic concentrations and translocations may actually be the basis for the ergogenic effect.…”
Section: Discussionmentioning
confidence: 99%
“…Several investigators (18,27,40,59,63) have observed a positive relationship between the rate of efflux of hydrogen ions and lactate from the cell and the extracellular pH and HCO,-concentration. Recently, Roth and Brooks (52) identified a cell membrane lactate transporter and found that the rate of transport was directly related to the extracellular pH.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The intracellular accumulation of H + also depends on the extracellular H + concentration. H + efflux out of the muscle cell has been reported to be inhibited by extracellular acidosis 9 and enhanced by a greater extracellular buffer concentration 10 . It is therefore frequently hypothesized that increases in the extracellular buffer concentration, via the ingestion of an alkaline solution such as sodium bicarbonate 4 (NaHCO 3 ), may improve H + efflux out of the muscle cell and improve repeated-sprint performance 11 .…”
Section: Introductionmentioning
confidence: 99%
“…It is only slightly sensitive to internal pH but is strongly dependent on the external pH. Some authors have observed that alkalosis enhances (Hirche et al, 1975) and acidosis inhibits (Hirche et al, 1975;Spriet et al, 1985) the rate of lactate exit from the cell.…”
mentioning
confidence: 99%